Composite organic hydrogen-resistant coating for stainless steel and preparation method of composite organic hydrogen-resistant coating

By using a composite organic hydrogen resistance coating on 316L stainless steel material, combined with epoxy resin, curing agent, MoSe2 and nanomaterials, the existing coating has been solved, and the hydrogen resistance is poor, achieving efficient hydrogen Isolation effect and long life of the material.

CN119286361AActive Publication Date: 2025-01-10河南省锅炉压力容器检验技术科学研究院

Patent Information

Application Number
CN202411508166.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-10
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

The existing hydrogen-resistance coating has problems such as low bonding, poor thermal shock resistance, and easy cracking and peeling on 316L stainless steel materials. In addition, the organic hydrogen-resistance coating has few research and application, single chemical composition, and the hydrogen-resistance effect is not ideal. It is difficult to apply on a large scale in complex processes and special-shaped parts.

Method used

Using composite organic hydrogen resistance coating, the chemical components include epoxy resin, curing agent, MoSe2, silane-modified graphene and Ti3AlC2. Through magnetic stirring and vacuum drying oven drying process, a dense coating is formed to improve hydrogen resistance and bonding. Spend.

Benefits of technology

It has achieved a firm combination of the surface coating of 316L stainless steel material, low gas permeability and significant hydrogen resistance, reduced hydrogen permeability and diffusion, extended the service life of the material, reduced economic losses, and simple process and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286361A_ABST
    Figure CN119286361A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of organic coatings, in particular to a composite organic hydrogen-resistant coating for stainless steel and a preparation method thereof.The organic coating has an excellent hydrogen-resistant effect and meets the requirement of a stainless steel material for hydrogen resistance, the organic hydrogen-resistant coating comprises the chemical components of 40.5%-43.4% of epoxy resin, 28.9%-32.9% of a curing agent, 19.2%-24.8% of a diluent, 3.63%-4.13% of MoSe2, 0.21%-0.64% of silane modified graphene and 0.46%-1.07% of Ti3AlC2, the sum of the mass percentages of the chemical components is 100%. The prepared organic hydrogen-resistant coating is reasonable in chemical composition, good in hydrogen-resistant effect, simple in manufacturing method and easy to produce, and has remarkable production advantages, application value and social benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of organic coatings, and in particular to a composite organic hydrogen barrier coating for stainless steel and a preparation method thereof. Background Art

[0002] As a clean green energy, hydrogen energy has the advantages of being pollution-free, high in calorific value, and renewable and cyclical. It is hailed as the most promising secondary energy source in the future. However, the problem of hydrogen damage to hydrogen energy storage and transportation materials is one of the key problems currently restricting the industrialization of hydrogen energy. This is because metal materials have been in service for a long time in a high-pressure hydrogen-rich environment, and hydrogen inevitably enters the interior of the material through penetration and diffusion, making the material prone to problems such as hydrogen embrittlement and hydrogen damage, which seriously affects the stable operation of the hydrogen storage and transportation system, and even causes serious safety accidents, causing irreparable losses to people's lives and property.

[0003] Due to its excellent corrosion resistance and mechanical properties, 316L stainless steel is widely used in hydrogen storage equipment, reactor blanket structure and other fields. In order to reduce the corrosion and damage of hydrogen and its isotopes to austenitic stainless steel materials, a hydrogen barrier coating is generally prepared on the surface of the material to set a hydrogen permeation barrier, which plays a role in slowing down or preventing hydrogen and its isotopes from entering the substrate, thereby preventing the occurrence of hydrogen embrittlement and other phenomena. This is currently a relatively economical and effective means.

[0004] At present, the hydrogen barrier coatings used on a large scale are mainly ceramic coatings, including oxide coatings (Er2O3, Al2O3, ZrO2, SiO2, TiO2, Cr2O3, etc.) and non-oxidation coatings (TiN, Fe2N, AlN, TiC, SiC, etc.). They have good hydrogen barrier properties, and the preparation methods are mainly magnetron sputtering, chemical vapor deposition, micro-arc oxidation, plasma spraying, sol-gel method, etc. However, their preparation processes are often more complicated and demanding, and are not easy to be used on a large scale on pipelines and special-shaped parts. In addition, this type of hydrogen barrier coating and the substrate material also have problems such as low bonding, poor thermal shock resistance, and easy cracking and peeling.

[0005] With the development of new materials and new technologies, organic hydrogen barrier coatings have received more and more attention due to their excellent corrosion resistance, ideal mechanical properties and simple construction process. However, there are relatively few research and applications on organic hydrogen barrier coatings in China, and the existing organic hydrogen barrier coatings still have problems that need to be solved, such as the relatively single chemical composition of the hydrogen barrier coatings and the unsatisfactory hydrogen barrier effect. Summary of the invention

[0006] In view of the above-mentioned defects and problems, the present invention provides a composite organic hydrogen barrier coating for stainless steel and a preparation method thereof, which has a reasonable formula, a simple preparation process, and a good hydrogen barrier effect, and can be applied to the organic hydrogen barrier coating on the surface of 316L stainless steel material.

[0007] The solution adopted by the present invention to solve the technical problem is: a composite organic hydrogen barrier coating for stainless steel, wherein the chemical components of the composite organic hydrogen barrier coating are as follows: epoxy resin: 40.5-43.4%, curing agent: 28.9-32.9%, diluent: 19.2-24.8%, MoSe2: 3.63-4.13%, silane-modified graphene: 0.21-0.64%, Ti3AlC2: 0.46-1.07%, and the sum of the mass percentages of the chemical components is 100%.

[0008] Furthermore, the curing agent is polyamide 650, the diluent is a mixed solvent consisting of xylene and n-butanol, and the mass ratio of xylene to n-butanol is (6-7): (3-4) or 7:3.

[0009] Furthermore, the epoxy resin is bisphenol A epoxy resin, NbSe2 is nano NbSe2, and Ti2SnC is nano Ti2SnC.

[0010] Furthermore, the bisphenol A epoxy resin can be one of Baling Petrochemical E44, Phoenix 6101, Nanya 128, and Sanmu 828.

[0011] Furthermore, the mass percentages of the chemical components of the composite organic hydrogen barrier coating are: epoxy resin: 42.2%, curing agent: 29.5%, diluent: 23.2%, MoSe2: 3.8%, silane-modified graphene: 0.45%, Ti3AlC2: 0.85%, and the sum of the mass percentages of the chemical components totals 100%.

[0012] Furthermore, a method for preparing a composite organic hydrogen barrier coating for stainless steel, using a composite organic hydrogen barrier coating for stainless steel, is characterized in that it comprises the following steps: (1) Pretreatment of 316L stainless steel: Grind the base material with sandpaper or a grinder to remove scale, grease, etc. until the metallic luster is exposed. Then use anhydrous ethanol or acetone to remove surface oil and impurities, then wash with hot water and rinse with running water, and finally blow dry with a hot air blower; (2) preparing a diluent in proportion, then adding silane-modified graphene, MoSe2 and Ti3AlC2 into the diluent, stirring for 15 to 30 minutes at a speed of 500 to 800 rpm using a magnetic stirrer, and obtaining a solution A after being fully mixed; (3) adding epoxy resin weighed in proportion to solution A, stirring at 800 to 1100 rpm with a magnetic stirrer for 20 to 40 minutes, and mixing thoroughly to obtain solution B; (4) Add the curing agent weighed in proportion to solution B, and stir at 500-750 rpm for 2-3 h using a magnetic stirrer to mix evenly; (5) The mixed solution B is brushed onto the surface of the 316L stainless steel material, and then placed in the air to dry naturally for 12 to 18 hours, and then placed in a vacuum drying oven at 50 to 65° C. to dry for 24 to 30 hours. After being taken out, it is naturally cured at room temperature to obtain a composite organic hydrogen barrier coating.

[0013] Furthermore, the prepared composite organic hydrogen barrier coating has a thickness of 0.10 to 0.30 mm.

[0014] Furthermore, when preparing the diluent, the stirring rate is 700 rpm and the stirring is performed for 20 minutes.

[0015] Beneficial effects of the present invention: The composite organic hydrogen barrier coating of the present invention not only has a firm bond with the surface of the 316L stainless steel material, but also has a dense coating structure, low gas permeability, and good hydrogen barrier effect. This is largely due to the silane-modified graphene, MoSe2 and Ti3AlC2 introduced into the coating of the present invention. The combined effect of the three can effectively improve the hydrogen barrier effect of the organic coating: first, the nano-scale sheet structure of the silane-modified graphene can directly block hydrogen penetration, and is also a good hydrogen trap, thereby blocking hydrogen penetration; secondly, MoSe2 and Ti3AlC2 have unique nano-layered Crystal structure can hinder the diffusion of hydrogen in the coating and improve the hydrogen barrier performance of the coating; thirdly, silane-modified graphene can also improve the crystallinity and density of epoxy resin and reduce the defects in the epoxy resin coating, which is beneficial to improve the bonding degree between the organic hydrogen barrier coating and the 316L stainless steel material and the hydrogen barrier effect of the coating; through the composite organic hydrogen barrier coating and the 316L stainless steel material are firmly bonded, the coating structure is dense, which can effectively reduce or even prevent the hydrogen damage problem of the 316L stainless steel material; at the same time, the chemical composition of the organic hydrogen barrier coating is scientific, the cost is low, the preparation method is simple, easy to implement, and it has significant production advantages and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a morphology diagram of the unmodified graphene used in the present invention.

[0017] Figure 2 This is a morphology image of the silane-modified graphene prepared in the present invention.

[0018] Figure 3This is a morphology diagram of the adhesion test experiment of the composite organic hydrogen barrier coating for stainless steel prepared by the present invention. DETAILED DESCRIPTION

[0019] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0020] Example 1. In the specific implementation of the present invention, the chemical components of the composite organic hydrogen barrier coating are as follows: epoxy resin (Baling Petrochemical E44): 42.2%, curing agent (polyamide 650): 29.5%, diluent: 23.2%, MoSe2: 3.8%, silane-modified graphene: 0.36%, Ti3AlC2: 0.94%, and the sum of the mass percentages of each chemical component is 100%.

[0021] The diluent is a mixed solvent of xylene and n-butanol, and the mass ratio of xylene to n-butanol is 7:3.

[0022] The preparation method comprises the following steps: (1) Pretreatment of 316L stainless steel material: The base material is polished with 400#, 600#, 800#, and 1000# sandpaper in turn to remove oxide scale, grease, etc. until the metallic luster is exposed. Then, the surface oil and impurities are removed with anhydrous ethanol, and then washed with hot water and running water, and finally dried with a hot air blower; (2) preparing a diluent in proportion, then adding silane-modified graphene, MoSe2 and Ti3AlC2 into the diluent, stirring for 20 min at a speed of 500 rpm using a magnetic stirrer, and obtaining a solution A after being fully mixed; (3) adding epoxy resin (Baling Petrochemical E44) weighed in proportion to solution A, stirring at 800 rpm with a magnetic stirrer for 35 min, and mixing thoroughly to obtain solution B; (4) Add the curing agent (polyamide 650) weighed in proportion to solution B, and stir at 700 rpm for 2 h using a magnetic stirrer to mix evenly; (5) The mixed solution B was brushed onto the surface of 316L stainless steel material with a coating thickness of 0.2 mm, and then placed in the air to dry naturally for 12 h, and then placed in a vacuum drying oven at 60°C for 24 h. After being taken out and naturally cured at room temperature, a composite organic hydrogen barrier coating was obtained after trimming.

[0023] The composite organic hydrogen barrier coating provided in this embodiment is firmly bonded to the 316L stainless steel material, and the coating structure is dense, which can effectively reduce or even prevent the hydrogen damage problem of the 316L stainless steel material; at the same time, the organic hydrogen barrier coating has a scientific chemical composition, low cost, simple preparation method, easy implementation, and has significant production advantages and social benefits.

[0024] Example 2: A composite organic hydrogen barrier coating for stainless steel and a preparation method thereof are described with the differences from Example 1 as the center.

[0025] In this embodiment, the chemical components of the composite organic hydrogen barrier coating are as follows: epoxy resin (Nan Ya 128): 41.5%, curing agent (polyamide 650): 31.9%, diluent: 21.3%, MoSe2: 4.03%, silane-modified graphene: 0.55%, Ti3AlC2: 0.72%, and the sum of the chemical components by mass percentage is 100%.

[0026] The diluent is a mixed solvent of xylene and n-butanol, and the mass ratio of xylene to n-butanol is 7:3.

[0027] The preparation method comprises the following steps: (1) Pretreatment of 316L stainless steel: Grind the base material with 400#, 600#, 800#, and 1000# sandpaper in turn to remove oxide scale, grease, etc. until the metallic luster is exposed. Then use anhydrous ethanol or acetone to remove surface oil and impurities, then wash with hot water and rinse with running water, and finally blow dry with a hot air blower; (2) preparing a diluent in proportion, then adding silane-modified graphene, MoSe2 and Ti3AlC2 into the diluent, stirring for 18 min at 600 rpm using a magnetic stirrer, and obtaining solution A after being fully mixed; (3) adding epoxy resin (Nan Ya 128) weighed in proportion to solution A, stirring at 900 rpm for 30 min using a magnetic stirrer, and mixing thoroughly to obtain solution B; (4) Add the curing agent (polyamide 650) weighed in proportion to solution B, and stir at 600 rpm for 2.5 h using a magnetic stirrer to mix evenly; (5) The mixed solution B was brushed onto the surface of 316L stainless steel material with a coating thickness of 0.25 mm, and then placed in the air to dry naturally for 14 h, and then placed in a vacuum drying oven at 58°C for 26 h. After being taken out and naturally cured at room temperature, a composite organic hydrogen barrier coating was obtained after trimming.

[0028] Example 3: A composite organic hydrogen barrier coating for stainless steel and a preparation method thereof are described with the differences from Example 1 as the center.

[0029] In this embodiment, the chemical components of the composite organic hydrogen barrier coating are as follows: epoxy resin (Sanmu 828): 41.8%, curing agent (polyamide 650): 29.0%, diluent: 24.2%, MoSe2: 3.96%, silane-modified graphene 0.42%, Ti3AlC2: 0.62%, and the sum of the chemical components by mass percentage is 100%.

[0030] The diluent is a mixed solvent of xylene and n-butanol, and the mass ratio of xylene to n-butanol is 7:3.

[0031] The preparation method comprises the following steps: (1) Pretreatment of 316L stainless steel material: The base material is polished with 400#, 600#, 800#, and 1000# sandpaper in turn to remove oxide scale, grease, etc. until the metallic luster is exposed. Then, acetone is used to remove surface oil and impurities, and then it is washed with hot water and rinsed with running water, and finally dried with a hot air blower; (2) preparing a diluent in proportion, then adding silane-modified graphene, MoSe2 and Ti3AlC2 into the diluent, stirring for 25 min at 750 rpm using a magnetic stirrer, and obtaining a solution A after being fully mixed; (3) adding epoxy resin (Sanmu 828) weighed in proportion to solution A, stirring at 1000 rpm for 35 min using a magnetic stirrer, and mixing thoroughly to obtain solution B; (4) Add the curing agent (polyamide 650) weighed in proportion to solution B, and stir at 750 rpm for 3 h using a magnetic stirrer to mix evenly; (5) The mixed solution B was brushed onto the surface of 316L stainless steel material with a coating thickness of 0.30 mm, and then placed in the air to dry naturally for 16 h, and then placed in a vacuum drying oven at 60°C for 30 h. After being taken out and naturally cured at room temperature, a composite organic hydrogen barrier coating was obtained after trimming.

[0032] Performance Test: Under room temperature conditions, an electrochemical hydrogen permeation experiment was conducted on the composite organic hydrogen barrier coatings prepared in Examples 1-3 above. The test results are as follows: 1. The composite organic hydrogen barrier coating prepared according to the ratio and method described in Example 1 has a hydrogen permeation resistance 83 times that of 316L stainless steel. The coating has an excellent hydrogen barrier effect. After the electrochemical hydrogen permeation experiment, the surface of the organic coating is in good condition and is firmly bonded to the 316L stainless steel. In addition, the organic coating bonding strength test was evaluated using a grid knife. The results showed that the organic hydrogen barrier coating and the 316L stainless steel material were tightly bonded, reaching the ISO grade O and ASTM grade 5B standards; 2. The composite organic hydrogen barrier coating prepared according to the ratio and method described in Example 2 has a hydrogen permeation resistance that is 90 times that of 316L stainless steel. The coating has an excellent hydrogen barrier effect. After the electrochemical hydrogen permeation experiment, the surface of the organic coating is in good condition and is firmly bonded to the 316L stainless steel. In addition, a hundred-grid knife was used to test and evaluate the bonding strength of the organic coating. The results showed that the organic hydrogen barrier coating and the 316L stainless steel substrate were tightly bonded, reaching the ISO grade O and ASTM grade 5B standards; 3. The composite organic hydrogen barrier coating prepared according to the ratio and method described in Example 3 has a hydrogen permeation resistance that is 87 times that of 316L stainless steel. The coating has an excellent hydrogen barrier effect. After the electrochemical hydrogen permeation experiment, the surface of the organic coating is in good condition and is firmly bonded to the 316L stainless steel. In addition, the organic coating bonding strength test was evaluated using a grid knife. The results showed that the organic hydrogen barrier coating and the 316L stainless steel substrate were tightly bonded, reaching the ISO grade O and ASTM grade 5B standards. Using the composite organic hydrogen barrier coating for stainless steel and its preparation method described in the present invention, the organic hydrogen barrier coating was prepared on 316L stainless steel material many times, and the composite organic hydrogen barrier coating was tested for relevant performance, and similar or identical experimental results were obtained. The above experimental results prove that the composite organic hydrogen barrier coating for stainless steel described in the present invention can effectively reduce the penetration of hydrogen into 316L stainless steel material, thereby reducing or even preventing the hydrogen damage problem of 316L stainless steel material, improving the safety and reliability of hydrogen storage and transportation equipment materials, and the service life of 316L stainless steel material is increased by 5 to 10 times on the original basis, greatly reducing the economic losses caused by hydrogen damage to the material, and reducing the operating costs of the enterprise.

[0033] In summary, the composite organic hydrogen barrier coating for stainless steel provided by the present invention has good hydrogen barrier effect, reasonable formula, low preparation cost, simple preparation process, easy implementation, significant production advantages and social benefits, and is an innovation in the design and application of organic hydrogen barrier coatings.

[0034] The above description is only a preferred embodiment of the present invention and does not limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A composite organic hydrogen barrier coating for stainless steel, characterized in that: The chemical components of the composite organic hydrogen barrier coating are as follows: epoxy resin: 40.5-43.4%, curing agent: 28.9-32.9%, diluent: 19.2-24.8%, MoSe2: 3.63-4.13%, silane-modified graphene: 0.21-0.64%, Ti3AlC2: 0.46~1.07%, the sum of the mass percentages of each chemical component is 100%.

2. The composite organic hydrogen barrier coating for stainless steel according to claim 1, characterized in that: The curing agent is polyamide 650, the diluent is a mixed solvent consisting of xylene and n-butanol, and the mass ratio of xylene to n-butanol is (6-7): (3-4) or 7:

3.

3. The composite organic hydrogen barrier coating for stainless steel according to claim 1, characterized in that: The epoxy resin is bisphenol A epoxy resin, the NbSe2 is nano NbSe2, and the Ti2SnC is nano Ti2SnC.

4. The composite organic hydrogen barrier coating for stainless steel according to claim 3, characterized in that: The bisphenol A type epoxy resin can be one of Baling Petrochemical E44, Phoenix 6101, Nanya 128, and Sanmu 828.

5. The composite organic hydrogen barrier coating for stainless steel according to claim 1, characterized in that: The chemical composition weight percentage of the composite organic hydrogen barrier coating is as follows: epoxy resin: 42.2%, curing agent: 29.5%, diluent: 23.2%, MoSe2: 3.8%, silane-modified graphene: 0.45%, Ti3AlC2: 0.85%, the sum of the mass percentages of each chemical component is 100%.

6. A method for preparing a composite organic hydrogen barrier coating for stainless steel, using the composite organic hydrogen barrier coating for stainless steel as claimed in claims 1 to 5, characterized in that: The following steps are involved: (1) Pretreatment of 316L stainless steel: Grind the base material with sandpaper or a grinder to remove scale, grease, etc. until the metallic luster is exposed. Then use anhydrous ethanol or acetone to remove surface oil and impurities, then wash with hot water and rinse with running water, and finally blow dry with a hot air blower; (2) preparing a diluent in proportion, then adding silane-modified graphene, MoSe2 and Ti3AlC2 into the diluent, stirring for 15 to 30 minutes at a speed of 500 to 800 rpm using a magnetic stirrer, and obtaining a solution A after being fully mixed; (3) adding epoxy resin weighed in proportion to solution A, stirring at 800 to 1100 rpm with a magnetic stirrer for 20 to 40 minutes, and mixing thoroughly to obtain solution B; (4) Add the curing agent weighed in proportion to solution B, and stir at 500-750 rpm for 2-3 h using a magnetic stirrer to mix evenly; (5) The mixed solution is brushed onto the surface of 316L stainless steel material, and then placed in the air to dry naturally for 12 to 18 hours, and then placed in a vacuum drying oven at 50 to 65° C. to dry for 24 to 30 hours. After being taken out, it is naturally cured at room temperature to obtain a composite organic hydrogen barrier coating.

7. The method for preparing a composite organic hydrogen barrier coating for stainless steel according to claim 6, characterized in that: The thickness of the prepared composite organic hydrogen barrier coating is 0.10-0.30 mm.

8. The method for preparing a composite organic hydrogen barrier coating for stainless steel according to claim 6, characterized in that: When preparing the diluent, the stirring rate is 700 rpm and the stirring is for 20 minutes.

Citation Information

Patent Citations

  • Anti-hydrogen corrosion-resistant coating and preparation method

    CN107916045A

  • Method for preparing steel structure aqueous corrosion-resistant fireproof coating material

    CN108314951A

  • Anticorrosive coating with barrier property

    CN109762462A

  • Organic hydrogen permeation-resistant coating as well as preparation method and application thereof

    CN115093769A

  • Hydrogen-resistant composite coating and preparation method thereof

    CN115704090A

Cited By

  • Hydrogen-resistant coating paint and hydrogen conveying pipeline

    CN120699508A